Seeing What Needs to be Seen, Saying What Needs to be Said: Discourse Analysis for Critical Adult Education - Kim L. Niewolny; Arthur L. Wilson (Adult Education Research Conference, 2008)
We explore several prominent traditions of discourse analysis and their potential for critical scholarship in adult education. Conclusions include key insights for adult educators to engage with the theory and practice of conducting discourse analysis.
Keywords: discourse analysis; critical adult education; theory and method